Discussion groups with teenagers: a speech subjectivised in the school (Fractal: Journal of Psychology, 2009)
In connection with "Copsy-enfant" (French National Agency for Research, 2006-2009), our recent research on the construction of gender and generational identity among teenagers, we set up seven discussion groups for middle and high school students in a working-class neighborhood of metropolitan Paris. The purpose of this article is to situate our research within the context of today's interrogations on adolescence. Such groups provided for the teenagers who requested them, a space within the school reducing the gap between their pupil's status and their teenager's being Subject. In this paper, we speak about the structuration of these groups whose orientation was psychoanalytic. We address the containing function and the social bonds that such groups provided for the teenagers.